Effects of muscular strength, exercise order, and acute whole-body vibration exposure on bat swing speed - Reyes, G. F. C.; Dickin, D. C.; Dolny, D. G.; Crusat, N. J. K. (The Journal of Strength and Conditioning Research, 2010)
The purposes for this study were to investigate effects of acute whole-body vibration (WBV) exposure and exercise order on bat speed and to examine relationship between muscular strength and bat speed. All participants were recreationally trained men (n = 16; 22 ± 2 years; 181.4 ± 7.4 cm; 84.7 ± 9 kg), with previous baseball experience and were tested for 1 repetitive maximum (1RM) strength in squat and bench press. Subjects then participated in 4 randomized sessions on separate days, each consisting of 3 sets of 5 bat swings. Exercises (upper and lower body dynamic and static movements related to bat swing) with or without WBV exposure were performed after sets 1 and 2. Trials were as follows: no-exercise Control (CTRL), upper body followed by lower body exercises without WBV (Arm-Leg NOVIB), upper body followed by lower body exercises with WBV (Arm-Leg VIB), and lower body followed by upper body exercises with WBV (Leg-Arm VIB). Bat speed was recorded during each swing and averaged across sets. Statistical analyses were performed to assess differences across sets and trials. Linear regressions analyzed relationship between strength and bat speed. A significant relationship existed between bat speed and lower body strength (r2 = 0.406, p = 0.008) but not for upper body strength. The exercise order of Arm-Leg VIB significantly increased bat speed by 2.6% (p = 0.02). Performing identical order of exercises without vibration (Arm-Leg NOVIB) significantly decreased bat speed by 2% (p = 0.039). It was concluded that adding vibration exposure to total-body exercises can provide acute enhancements in bat speed. Additionally, leg strength was shown to influence bat speed suggesting that increasing leg strength may enhance bat speed.